2018
DOI: 10.3390/ma11102054
|View full text |Cite
|
Sign up to set email alerts
|

Wear Resistance Mechanism of Alumina Ceramics Containing Gd2O3

Abstract: Excellent wear resistance of alumina ceramics is a desirable quality for many products. The purpose of this work was to improve the wear resistance of 99% alumina ceramics in an Al2O3–Gd2O3–SiO2–CaO–MgO (AGSCM) system. The content of Gd2O3 varied from 0.01% to 1%. A test of wear rate was performed in a ball milling apparatus in a water environment according to the Chinese industry standard. The compositions and microstructure of this material, as well as the effect of bulk density on wear rate, were studied. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Comparing Sc 2 O 3 with Gd 2 O 3 11 and Lu 2 O 3 , 12 it is found that their effects on the wear rate of ceramics are similar. The wear resistance of ceramics containing Lu is slightly better.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Comparing Sc 2 O 3 with Gd 2 O 3 11 and Lu 2 O 3 , 12 it is found that their effects on the wear rate of ceramics are similar. The wear resistance of ceramics containing Lu is slightly better.…”
Section: Discussionmentioning
confidence: 93%
“…Different rare earths have different effects on the wear resistance of ceramics. [11][12][13][14][15][16][17] In this paper, we studied the effect of Sc 2 O 3 on the wear resistance of Al 2 O 3 ceramics. In the periodic table, there is no connection between Al and Sc, but the properties of Sc are very close to Al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the primary material of the matrix of samples was alumina, which is a dielectric [66,67] or an n-type semiconductor [68] with a melting point of 2044 • C and a boiling point of 2977 • C [22,69].…”
Section: Electrical Properties and Electrical Discharge Machining Of mentioning
confidence: 99%
“…To be specific, MRI is a popular imaging technology due to its high-resolution morphological capabilities, non-invasiveness, and lack of risk of radiation damage [ 15 , 16 ]. More excitingly, incorporating the MRI contrast agents (e.g., gadolinium oxide (Gd 2 O 3 )) into nanosystems can extend the blood circulation time while endowing the nanosystems with MRI visibility by taking the shortened longitudinal proton relaxation time of the surrounding hydrogen protons [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%